1982
DOI: 10.1002/pssb.2221130116
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Local Density Approximation. Electron Density in Inversion Layers

Abstract: I n the local density approximation (LDA) the density of a many-electron system is expressed as a functionof the spatially varying potential. Here a modifiedLDA is derived applicable for a potential with a high step a t some plane which is e.g. a model for the band edges in an inversion layer a t the semiconductor-insulator interface. The local density of states shows oscillations and decreases t o zero a t the interface as a consequence of quantum mechanical reflection. Simple expressions for the density are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(88 citation statements)
references
References 17 publications
3
85
0
Order By: Relevance
“…Therefore, a compromise solution will be to calibrate the DG quantum corrections [36] to the PS charge distribution and then use the DG simulations. Although other techniques, such as MLDA [37], have been proposed in the literature and are available in other commercial software [38], a comparison of the several simulation models is outside the scope of this paper. The DG formalism introduces an additional quantum correction term, ψ qm , which is proportional to the second derivative of the square root of the carrier density…”
Section: Density Gradient Calibrationmentioning
confidence: 99%
“…Therefore, a compromise solution will be to calibrate the DG quantum corrections [36] to the PS charge distribution and then use the DG simulations. Although other techniques, such as MLDA [37], have been proposed in the literature and are available in other commercial software [38], a comparison of the several simulation models is outside the scope of this paper. The DG formalism introduces an additional quantum correction term, ψ qm , which is proportional to the second derivative of the square root of the carrier density…”
Section: Density Gradient Calibrationmentioning
confidence: 99%
“…7 The position of the surface Fermi level, well above the CBM, indicates a downward band bending relative to the Fermi level at the surface, leading to electron accumulation for all wurtzite samples measured. To investigate this further, the band bending profile and corresponding electron accumulation in the surface space-charge region was determined by solving Poisson's equation numerically within the modified Thomas-Fermi approximation ͑MTFA͒ following the method described by Veal et al 17 The MTFA correction has been shown 18 to yield profiles that are in good agreement with those obtained from full self-consistent Poisson-Schrödinger calculations. The resulting profiles are shown in Fig.…”
mentioning
confidence: 99%
“…The gate capacitance was calculated using the Taurus-DAVINCI with a three-dimensional SiNW FET structure. Quantum-mechanical effects were introduced using the modified local density approximation (MLDA) method [22,23]. We used the MLDA method in [22,23] instead of an improved method described in the appendix of [22] because of shorter calculation time of the prior method.…”
Section: Computer Simulation Proceduresmentioning
confidence: 99%